The Efficacy of Capsaicin on Sleep Quality and Fatigue in Fibromyalgia. (3rd April 2022) - Elijah, Joseph; Powell, Kelly; Smith, Michael A.
Abstract: Capsaicin is a topical pain reliever that has been evaluated by randomized controlled trials (RCTs) as a potential adjunctive therapy for treating unmitigated fibromyalgia. Therefore, a review of English articles using PubMed and Embase was conducted from January 1, 1990 to February 9, 2022 in order to evaluate the utility of capsaicin for improvement of sleep quality and fatigue associated with fibromyalgia. The search terms included: "fibromyalgia" and "capsaicin". Articles included were RCTs evaluating capsaicin in adult patients with fibromyalgia. Two studies met criteria and included 175 patients that received either capsaicin or placebo for an average total treatment length of 5 weeks. The treatment outcomes assessed were changes in quality of sleep and fatigue by several standardized modalities. These include visual analog scale (VAS) of sleep quality and fatigue, fatigue severity scale, Pittsburgh Sleep Quality Index (PSQI), and global subjective improvement. Both studies demonstrated no changes in sleep quality, but one study did find a significant difference in global subjective improvement. This same study also found a significant improvement in fatigue. Consequently, this existing evidence is insufficient to warrant recommending capsaicin as adjunctive therapy for improvement in sleep quality and fatigue. Future studies regarding capsaicin therapy for fibromyalgia are needed.